PERLINDUNGAN HUKUM TERHADAP PEKERJA YANG MEMPEROLEH PEMUTUSAN HUBUNGAN KERJA DITINJAU DARI UNDANG-UNDANG NOMOR 11 TAHUN 2020 TENTANG CIPTA KERJA - Cagla Yasemin Goren; Ahmad Redi (Fakultas Hukum Universitas Tarumanagara, 2021)
In Indonesia, the regulation on Employment is prescribed in Law Number 11 of 2003 concerning Employment. In 2020, the government enforced Law Number 11 of 2020 on Job Creation (Cipta Kerja). Since the law involves various sectors, the Job Creation Law is often dubbed as